PERSPEKTIF ANAK-ANAK TENTANG KEKERASAN DOMESTIK - Namirah, Namirah (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2023)
This study explores children's perceptions of domestic violence and its impact on their psychological and social health. Through in-depth interviews and observations, the study revealed that children exposed to domestic violence often experience deep trauma, fear, and prolonged anxiety. These children also show difficulty in establishing healthy social relationships and often develop reactive coping strategies. The results highlight the importance of comprehensive interventions and holistic support to help these children recover from their traumatic experiences. The study also emphasizes the need for collaboration between families, schools, and communities in creating a safe and supportive environment for the development of children affected by domestic violence.